ISLAMIC CHARACTER FOR ELEMENTARY SCHOOL STUDENTSIN DIGITAL ERA (International Conference on Elementary Education, 2018)
This study aims to examine the importance of Islamic character for elementary school students in the digital age. The development of technology towards all digital is now increasingly rapid. In this digital era, humans generally have a new lifestyle that cannot be separated from all-electronic devices. The digital era has brought many good changes as a positive impact that can be used as well as possible. But at the same time, the digital era also has a lot of negative impacts, so it becomes a new challenge in human life in this digital era. These negative impacts are exposed to elementary school age students. The world of children is very concerning, especially in changing character and mentality. The attitude of children who are aggressive and physical violence is often witnessed in association with each other is an interconnected phenomenon. Strengthening Islamic character must be built as a strong foundation in a child to reduce the negative impact of the digital era. Synergy between family environment and school environment is needed in strengthening Islamic character. Family is very necessary to build a community of learners about children's education, and is very necessary to become an education policy in an effort to build Islamic character. While the school is an educational institution that is responsible for forming characters, to mature humans with good attitudes, behaviors, and morals so that a strong generation of Islam is born.